Ethnobotanical Study of Medicinal Plants Used to Treat Degenerative Disease in East Lombok - Dyke Gita Wirasisya; Nisa Isneni Hanifa; Wahida Hajrin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2020)
Degenerative diseases have become a complex problem around the world. Until now, degenerative diseases have become the biggest cause of death in the world. Approximately, 17 million people die early each year due to the global epidemic of degenerative diseases. Peoples in developing countries still rely on medicinal plants for primary health care. The knowledge for medicinal plant were passed down through generation with little written documentation. This study aimed to document the indigenous medicinal plants used for the treatment for degenerative diseases in East Lombok, Indonesia and to find leads on prospective plants for further ethnopharmacology research based on quantitative ethnobotany index. The ethnomedicinal data were collected through interview and discussion among local healers and plant collected with the help of local guide also herbarium was made to aid specimen confirmation. Ethnomedicinal data was analyzed using use value (UV) along with fidelity level (FL). A total of 20 informants (traditional healers) were interviewed and from the study we can documented the use of 63 plants for the treatment of degenerative diseases. The UV ranged from 0,05 (Sesbania grandiflora) to 0,35 (Carica papaya), while the highest FL (100%) was found for 29 species. Based on the ethnobotanical index (UV and FL) from each plant we can recommend 15 species for further ethnopharmacological study to determine their therapeutic effects and mechanism of action. This study revealed rich ethnomedicinal knowledge from the community in East Lombok for the treatment of degenerative disease.ÃÂ